Development of Arthropod Morphological Identification Media - Eva Malahayati; Luthfiya Aqidatu Sholikhah (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2023)
Background: Invertebrate Zoology practicum activities require students to identify and classify types of invertebrate animals found in the environment. Phylum Arthropoda as a member of invertebrate animals had a very high number and diversity. Students had difficulties identifying arthropods using general biology books and articles from online journals that only provide general and incomplete information. The research objective was to develop android-based arthropod morphological identification media. Methods: This study used the Borg & Gall development model with stages of 1) potential and problems, 2) data collection, 3) design, 4) design validation, and 5) design revision. Design validation was assessed by the experts’ material and media experts. Validation results data has been analyzed by transforming the average of all aspects of observation qualitatively. Results: The results of the material expert validation of the arthropod morphological identification media amounted to 88.89 which was very worthy and the media experts gave an assessment of 87.5 which was very worthy. Conclusion: Media of Arthropod morphological identification to apply in invertebrate zoology practicum. Keywords : Media; Morphological Identification; Arthropoda